Plasma Cyclic Guanosine Monophosphate Is a Promising Biomarker of Clinically Significant Portal Hypertension in Patients With Liver Cirrhosis - Sturm, Lukas; Bettinger, Dominik; Roth, Lisa; Zoldan, Katharina; Stolz, Laura; Gahm, Chiara; Huber, Jan Patrick; Reincke, Marlene; Kaeser, Rafael; Boettler, Tobias; Kreisel, Wolfgang; Thimme, Robert; et al. (Frontiers in Medicine, 2022)
Introduction: Despite intensive research, reliable blood-derived parameters to detect clinically significant portal hypertension (CSPH) in patients with cirrhosis are lacking. As altered homeostasis of cyclic guanosine monophosphate (cGMP), the central mediator of vasodilatation, is an essential factor in the pathogenesis of portal hypertension, the aim of our study was to evaluate plasma cGMP as potential biomarker of cirrhotic portal hypertension. Methods: Plasma cGMP was analyzed in cirrhotic patients with CSPH (ascites, n = 39; esophageal varices, n = 31), cirrhotic patients without CSPH (n = 21), patients with chronic liver disease without cirrhosis (n = 11) and healthy controls (n = 8). cGMP was evaluated as predictor of CSPH using logistic regression models. Further, the effect of transjugular intrahepatic portosystemic shunt (TIPS) placement on plasma cGMP was investigated in a subgroup of cirrhotic patients (n = 13). Results: Plasma cGMP was significantly elevated in cirrhotic patients with CSPH compared to cirrhotic patients without CSPH [78.1 (67.6–89.2) pmol/ml vs. 39.1 (35.0–45.3) pmol/l, p < 0.001]. Of note, this effect was consistent in the subgroup of patients with esophageal varices detected at screening endoscopy who had no prior manifestations of portal hypertension (p < 0.001). Cirrhotic patients without CSPH displayed no significant elevation of plasma cGMP compared to patients without cirrhosis (p = 0.347) and healthy controls (p = 0.200). Regression analyses confirmed that cGMP was an independent predictor of CSPH (OR 1.042, 95% CI 1.008–1.078, p = 0.016). Interestingly, portal decompression by TIPS implantation did not lead to normalization of plasma cGMP levels (p = 0.101). Conclusions: Plasma cGMP is a promising biomarker of CSPH in patients with cirrhosis, especially with respect to screening for esophageal varices. The lacking normalization of plasma cGMP after portal decompression suggests that elevated plasma cGMP in cirrhotic portal hypertension is mainly a correlate of systemic and splanchnic vasodilatation, as these alterations have been shown to persist after TIPS implantation.